Kiat Menjinakkan Sel Kanker - Ferina Angelia; Yasavati Kurnia (Jurnal Kedokteran Meditek, 2011)
AbstrackCancer lies dormant in all of us. Like all living organisms, our bodies are making defective cells all the time. That’s how tumours are born. But our bodies are also equipped with a number of mechanisms that detect and keep such cells in check. People whose immune system is particularly active seem to be protected against cancer cells. Micro-tumours also cannot change into dangerous cancers without creating a new network of blood vessels to feed them. Today many drugs similar to angiostatin are being developed by the pharmaceutical industry. But their effects on humans when used alone have turned out to be disappointing. As an alternative, there are natural approaches that have a powerful effect on angiogenesis, without side effects, including common edible mushrooms, certain green teas, spices and herbs. As a conclusion, proper diet, peaceful mind and exercise are approaches that reinforcing the body’s defence mechanisms to keep the cancer at bay.Key words : cancer cells, angiogenesis, natural approaches